Physical characteristics study of dry leaves as liquid fuels application / Wan Norfarhana Wan Mansor - Wan Mansor, Wan Norfarhana (2018)
The study of dry leaves as a liquid fuels application gives the potential to solve the depletion and environmental issue of the oil resources. The abundancy of dry leaves nationwide make it one of the efficient, reliable and sustainable potential sources of energy. Several basic analysis such as heating value, proximate and ultimate analysis are used to analyze the dry leaves properties as a fuel. The results indicate that dry leaves have the heating value of 19.17 MJ/kg while the proximate analysis of dry leaves show that it contains 9.33% moisture, 62.67% volatile matter, 3.67% ash and 24.33% fixed carbon. Elemental analysis conducted on dry leaves gives the values of 75.94% C, 9.81% H, 0.22% N and 14.02% O. Dry leaves have relatively low H:C and O:C ratio, which are 1.55 and 0.16 respectively. Lower ratio indicates that it contain higher energy density and greater amount of heating value. Results obtained were compared to previous literature studies and the samples had a consistent value with the previous reports.